Types, prevalence, management, and outcome of maxillofacial tumors - Shawly, Hussam Hussain; Softah, Wed Abdulrahman; Sharrahi, Haitham Mohammed; Alenezi, Asma Husain; Alshaibani, Zayed Monif; Alruwili, Raghad Alrawi; AlOtaibi, Turki Ayyad; Alamer, Seham Saleh; Alsanea, Abdulrahman Ibrahim; Alshammari, Shoug Mefawez; Khojah, Alaa Abdulhamid (International Journal Of Community Medicine And Public Health, 2023)
Maxillofacial tumors constitute a diverse group of pathologic disorders with various histological types and clinical behaviours. The causes of head and neck tumors involve a combination of environmental factors and genetic predisposition. Although less frequent in children and adolescents, they still represent approximately 3% to 10% of head and neck tumor cases worldwide. Accurate diagnosis and management are crucial for favourable outcomes. The tumors can be categorized into epithelial, soft tissue, odontogenic, hematologic, and bone tumors, each with distinct characteristics and treatment approaches. The prevalence of these tumors varies based on location, age, and gender. A multidisciplinary approach, including surgery, medical treatments, radiation therapy, and palliative care, is often required for managing these tumors. Prognosis and outcomes depend on tumor type, stage, and individual factors, with early diagnosis and appropriate management contributing to better results. Regular follow-up is essential to detect potential recurrence or metastasis early and provide timely intervention. Individualized evaluation and treatment by qualified medical professionals are vital due to the uniqueness of each case. This review discusses the classification, clinical features, histopathological characteristics, radiographic presentations, treatment options, and prognosis of maxillofacial tumors.